2016
DOI: 10.1155/2016/7801781
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Enhance the Differentiation of Human Switched Memory B Lymphocytes into Plasma Cells in Serum-Free Medium

Abstract: The differentiation of human B lymphocytes into plasma cells is one of the most stirring questions with regard to adaptive immunity. However, the terminal differentiation and survival of plasma cells are still topics with much to be discovered, especially when targeting switched memory B lymphocytes. Plasma cells can migrate to the bone marrow in response to a CXCL12 gradient and survive for several years while secreting antibodies. In this study, we aimed to get closer to niches favoring plasma cell survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…The LRSC and blood sample were stored at room temperature and processed within 24 hours. The isolation of PBMCs from the LRSC was performed as previously described . Briefly, individual LRSCs were back‐flushed using 40 mL of Hank's balanced salt solution (Gilco) supplemented with 10% anticoagulant citrate dextrose solution (USP formula A, Fenwal).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LRSC and blood sample were stored at room temperature and processed within 24 hours. The isolation of PBMCs from the LRSC was performed as previously described . Briefly, individual LRSCs were back‐flushed using 40 mL of Hank's balanced salt solution (Gilco) supplemented with 10% anticoagulant citrate dextrose solution (USP formula A, Fenwal).…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of PBMCs from the LRSC was performed as previously described. 6,35 Briefly, individual LRSCs were back-flushed using 40 mL of Hank's balanced salt solution (Gilco) supplemented with 10% anticoagulant citrate dextrose solution (USP formula A, Fenwal). The recovered PBMCs were isolated by centrifugation on a sterile medium for isolation of lymphocytes as recommended by the manufacturer (Ficoll-Paque Plus, GE Healthcare).…”
Section: Lrsc and Whole-blood Procurement And Handlingmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSC) in the human bone marrow microenvironment provide factors that support LLPC survival (9597). Cytokines of the TNF superfamily (BAFF, APRIL and TNF-α), IL-6 family, CD80/CD86, CD44 binding to hyaluronic acid, and VLA-4 binding to VCAM-1/fibronectin promote survival of plasma cells.…”
Section: Lessons From Human Studiesmentioning
confidence: 99%
“…In addition, it has been found in recent years that MSCs have immunomodulatory capacity and the potential to treat a variety of inflammation-related diseases (1)(2)(3). Currently, studies on immune regulation of T cells by MSCs have been extensively provided (1,4,5), but reports on the effects of MSCs on B cell function are rare and present conflicting data (2,(6)(7)(8)(9)(10)(11). Some studies have reported that MSCs can promote B cell proliferation, activation, differentiation and antibody secretion (7-9, 12, 13), while others have shown opposite effects (10,11,(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, studies on immune regulation of T cells by MSCs have been extensively provided ( 1 , 4 , 5 ), but reports on the effects of MSCs on B cell function are rare and present conflicting data ( 2 , 6 - 11 ). Some studies have reported that MSCs can promote B cell proliferation, activation, differentiation and antibody secretion ( 7 - 9 , 12 , 13 ), while others have shown opposite effects ( 10 , 11 , 14 - 18 ). The main reason for this contradiction is that the immune regulation mechanism of MSCs on B cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%